Identification of a direct interaction between the Fab domains of IgG antibodies and human FcRn upon IgG-FcRn complex formation - Esben Trabjerg; Jeannette Nilsen; Torleif Tollefsrud Gjølberg; Jan Terje Andersen; Alexander Leitner; Kasper D. Rand (Communications Biology)
Abstract IgGs have become successful drug scaffolds by combining specific target binding with the ability to induce cellular cytotoxicity. Furthermore, IgGs possess unusually long half-lives in the blood (2-3 weeks). IgGs achieve such extraordinary half-lives through a pH-dependent interaction with the FcRn-receptor whereby IgGs are recycled. No high-resolution structure of FcRn in complex with a full-length IgG is available, and the interaction was long thought to be mediated solely via the IgG-Fc. However, some IgGs with identical Fc-parts, but different Fab-domains, exhibit different half-lives, suggesting involvement of the Fab-domains in FcRn binding. Here, we employ structural mass spectrometry (HDX-MS and XL-MS) to explore the interaction of full-length IgGs with FcRn. HDX-MS and XL-MS experiments confirm an interaction between FcRn and the Fc-region of IgGs, through three cross-links between FcRn and the IgG-Fc-domain and a reduction in HDX in both the receptor and the Fc-region upon complex formation. However, FcRn-induced changes in HDX are also observed in the Fab-domains, supported by cross-links between the Fab-domains and the α3-domain of FcRn. Our results thus provide direct evidence for an IgG Fab-FcRn interaction. We envision that these results could advance the engineering of IgG-antibodies with tailored pharmacokinetics and enhanced efficacy.